Study the influence of distance in Artificial Potential Field (APF) for Autonomous Emergency Braking System (AEB) on longitudinal motion - Abdullah, Z.; Mohamad Heerwan, Piee; I M, Izhar; M A, Zakaria (IOP Publishing, 2020)
Autonomous Emergency Braking (AEB) is one of the common control systems used by the vehicle in order to avoid the collision from the obstacle. AEB performance optimize mostly on dry road surface at low and medium speed. The slip tire model was derived in this paper in order to find the coefficient of road friction. The tire-road friction coefficient is used for the braking limit which is 450 N.m. In order to increase the ability of an AEB during presence of obstacle in front of the vehicle, combination of Time-to-Collision (TTC) and artificial potential field (APF) are proposed in this study. When the APF value was surpassed the threshold distance, the AEB will activate by itself. The limit for APF was designed based on assuming the dry road friction (0.9) condition and with present of static obstacle in front of the vehicle in longitudinal lane. Thus, the AEB system was designed considering on the dry road friction condition, time for Front Collision Warning (FCW)as well as Braking was included for the limit APF is developed. The combination of an additional distance with the maximum safety distance in the APF system will create the minimum safe distance from obstacle which is in the range of 2.0 meter after the vehicle stop entirely. The additional distance is influence by the product of the constant time setting which is t_s1 and t_s2 with current velocity. Then, the simulation results show that the proposed control strategy can adapt to the dry tire-road friction coefficient on the road